2003
DOI: 10.1002/jmri.10333
|View full text |Cite
|
Sign up to set email alerts
|

High signal peripancreatic fat on fat‐suppressed spoiled gradient echo imaging in acute pancreatitis: Preliminary evaluation of the prognostic significance

Abstract: Purpose:To evaluate peripancreatic signal changes on fatsuppressed T1-weighted spoiled gradient echo images associated with acute pancreatitis and investigate potential utility in regards to relationship to clinical outcome. Materials and Methods:The abdominal MR images in 31 patients with acute pancreatitis were reviewed, and evaluated for the presence of elevated signal intensity within the peripancreatic fat on fat-suppressed T1-weighted spoiled gradient echo images; the degree of signal changes was graded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Further evaluation of a large number of cases is warranted to determine the correlation between the clinical outcomes of the patients with the mild forms of acute pancreatitis and the MR findings. Further, as previously shown by Martin et al (25), tissue characterization by MRI could be another discriminative factor in addition to CT assessment for predicting the prognosis or severity of acute pancreatitis.…”
Section: Discussionsupporting
confidence: 59%
“…Further evaluation of a large number of cases is warranted to determine the correlation between the clinical outcomes of the patients with the mild forms of acute pancreatitis and the MR findings. Further, as previously shown by Martin et al (25), tissue characterization by MRI could be another discriminative factor in addition to CT assessment for predicting the prognosis or severity of acute pancreatitis.…”
Section: Discussionsupporting
confidence: 59%
“…Data on the accuracy of CECT in diagnosing extrapancreatic or peripancreatic fat necrosis are conflicting. Although eight groups claimed that fat necrosis could not be determined reliably by CECT92, 106, 107, several studies demonstrated a good correlation between extrapancreatic findings on CECT and the presence of fat necrosis at operation or autopsy104, 108, 109.…”
Section: Resultsmentioning
confidence: 99%
“…Although eight groups claimed that fat necrosis could not be determined reliably by CECT 92,106,107 , several studies demonstrated a good correlation between extrapancreatic findings on CECT and the presence of fat necrosis at operation or autopsy 104,108,109 .…”
Section: Pancreatic Necrosismentioning
confidence: 99%